Labor development strategy in the bag industry - Dyah Maya Nihayah; Phany Ineke Putri; Karsinah Karsinah (Universitas Islam Indonesia, 2016)
The research aims to formulate strategies for improving the labor competencies in the bag industry in Kudus Regency. The data comprise business players, which will be analyzed using the Strength, Weaknesses, Opportunities, and Threats (SWOT) analysis. The results reveal that the proper strategy for improving employment in the bag industry is growth and build strategy. Growth and development strategy are intensive actions undertaken through the development of labor competencies to improve the quality of output. It can be made with creating learning resources by designing methods and trainings refer to the Competency Based Training (CBT).